Investigating Students' Reading Anxiety and Their Factors - Seliana, Tera; Larasaty, Gina; Anggrarini, Natalia; Efendi, Nasori (Jadila: Journal of Development and Innovation in Language and Literature Education, 2024)
This research aims to know what are the fators that lead students to reading anxiety in English foreign language and to know what are the level of anxiety. By using qualitative research, the data were obtained from questionnaires of both. This research was conduected with total 30 students at XI IPS 4 of SMAN 2 Indramayu. To get the data, reseracher used two questionnaires by Foreign Language Reading Anxiety Scale (FLRAS) questionnaire, contained to 26 statements for the factor reading anxiety and 20 statements for raeding level anxiety. After the data was found and it was calculated using the likert scale formula, the data was categorized based the interpretation. The result of this research showed that from the level of reading anxiety was found in the position high level of reading anxiety with score 50% (15 respondent) chose by students, other student 46,7% into medium level reading anxiety (14 respondent), and 3,3% into low level reading anxiety (1 respondent). And the factor that lead students reading anxiety were found fear of making errors as the biggest score 78%. Unfamiliar topic with mean 75%. Unknown vocabulary 74%. Unfamiliar culture 72%. And the lower factor that lead students in reading anxiety were worry about reading effect with mean 70%.